Testes de vigor para avaliação da qualidade fisiológica de sementes de Amburana cearensis (Allemão) A.C. Smith - Guedes, Roberta Sales (2012)
Amburana cearensis (Allemão) B.C. Smith is a species native to the Northeast region of Brazil. It has been increasingly exploited for fine woodworking, perfumery and medicine. The experiments were conducted in Laboratory of Analysis of Seeds in the Center of Agricultural Sciences of the Federal University of Paraiba, Areia - PB and Laboratory of Image Analysis and Seed Analysis, Department of Plant Production, College of Agriculture "Luiz de Queiroz", University of São Paulo in Piracicaba - SP, aimed to obtain information about of vigor of seed A. cearensis. In the first experiment were tested the accelerated aging test and the seed were exposed at 42 °C during 0, 24, 48, 72 and 96 h. For the second experiment were tested the electrical conductivity test and potassium leachate test. The factors considered for the electrical conductivity test were: soaking time (4, 8, 12, 16, 20 e 24 h) and volume of deionized water (75 and 100 mL) at a constant temperature of 25 °C. The potassium leachate test was carried out with samples of 50 seeds placed in plastic cups containing 75 mL of distilled water at 25 °C and the evaluations were performed at intervals 4, 8, 12, 16, 20 e 24 h. In the third experiment, seeds were subjected to X-rays test for evaluation of internal damage in seeds. A period of 48 h of aging was suitable for use in future studies to evaluate seed vigor A. cearensis, it is possible to detect significant differences between lots. The electrical conductivity test and potassium leachate test possible the discrimination of lots os seeds, it is recommended combinations for electrical conductivity of 75 mL/12 h and 100 mL/8 h and the leaching soaking for 4 h. Radiographic analysis is an effective instrument for monitoring A. cearensis seeds lots quality, because it is non-destructive and allows the prediction of seedling performance and enables the maintenance of high-quality seed.